Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1063/5.0084564
|View full text |Cite
|
Sign up to set email alerts
|

Beginnings of exciton condensation in coronene analog of graphene double layer

Abstract: Exciton condensation, a Bose–Einstein condensation of excitons into a single quantum state, has recently been achieved in low-dimensional materials including twin layers of graphene and van der Waals heterostructures. Here, we computationally examine the beginnings of exciton condensation in a double layer composed of coronene, a seven-benzene-ring patch of graphene. As a function of interlayer separation, we compute the exciton population in a single coherent quantum state, showing that the population peaks a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…More recently, the author [10] showed that the complete N -representability conditions are derivable from convex combinations of higher-particle, constraint matrices. In the past decade approximate conditions have been employed in variational calculations of the 2-RDM to solve significant problems such as the elucidation of the electronic properties of a glassy, highly conductive amorphous polymer [38] and the revelation of exciton condensation in molecular analogs of double-layer graphene [39][40][41][42] (refer to Refs. [43][44][45][46][47][48] for their use in one-particle RDM functional theories).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the author [10] showed that the complete N -representability conditions are derivable from convex combinations of higher-particle, constraint matrices. In the past decade approximate conditions have been employed in variational calculations of the 2-RDM to solve significant problems such as the elucidation of the electronic properties of a glassy, highly conductive amorphous polymer [38] and the revelation of exciton condensation in molecular analogs of double-layer graphene [39][40][41][42] (refer to Refs. [43][44][45][46][47][48] for their use in one-particle RDM functional theories).…”
Section: Introductionmentioning
confidence: 99%
“…At lower temperatures where quantum statistics dominate, the Mott transition is further facilitated by the favorable exchange interaction between like particles. Additionally, excitons may be regarded as weakly interacting neutral bosons and can thus form Bose–Einstein condensates (BECs) and superfluid phases . However, the transience of excitons often complicates experimental realization of such quantum phases.…”
Section: Introductionmentioning
confidence: 99%